Rachunek kosztów logistyki w przedsiębiorstwie handlowym - Skoczylas, Krystyna (Logistic Cost Account in Trade Companies, 2005)
The paper contains the information on the logistic cost account. The classification and register of costs of logistic are included. The advantage of proposed register of costs of logistic is included in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 300-306